Diagnóstico del clima laboral de la planta docente del Instituto Superior Tecnológico Loja, 2024 - Medina Jaramillo, Camila Fernanda (2025)
The work environment has become important over the years, since it is a fundamental basis for the atmosphere of the entities, favouring the performance and productivity of workers. This is why the present research entitled ‘Diagnosis of the work climate of the teaching staff of the Loja Higher Technological Institute, 2024’ was carried out in order to determine the current situation of the work climate of this entity, by means of a diagnosis. The first specific objective was to identify the main factors that have an impact on the work environment. The study of this objective helped to develop an improvement plan focused on the weaknesses found, seeking to address and improve these problems, generating a more productive and ergonomic working environment for teachers. This research was carried out using the deductive and analytical method, as this made it possible to identify trends and patterns, and thus to establish relationships between the different variables in order to formulate general conclusions; the techniques of surveys and interviews were used for this purpose. Thus, in general terms, the target population was 46 teachers hired through the Organic Law of Public Service (LOSEP). To conclude, and after analysing the data obtained in detail, it was determined that, in general terms, the working environment is adequate, as the results show that there are favourable factors for the institution, but at the same time, there are two factors that present inconsistencies, such as the physical factor with 44% and the interpersonal factor with 43%. This generates a slight dissatisfaction for the teachers, as part of their performance depends on the working environment.